Conjugate Photoelectron Energy Spectra Derived From Coincident FUV and Radio Measurements. Issue 23 (7th December 2021) - Urco, J. M.; Kamalabadi, F.; Kamaci, U.; Harding, B. J.; Frey, H. U.; Mende, S. B.; Huba, J. D.; England, S. L.; Immel, T. J.
Abstract: We present a method for estimating incident photoelectrons' energy spectra as a function of altitude by combining global scale far‐ultraviolet (FUV) and radio‐occultation (RO) measurements. This characterization provides timely insights important for accurate interpretation of ionospheric parameters inferred from the recently launched Ionospheric Connection Explorer (ICON) observations. Quantification of photoelectron impact is enabled by the fact that conjugate photoelectrons (CPEs) directly affect FUV airglow emissions but not RO measurements. We demonstrate a technique for estimation of photoelectron fluxes and their spectra by combining coincident ICON and COSMIC2 measurements and show that a significant fraction of ICON‐FUV measurements is affected by CPEs during the winter solstice. A comparison of estimated photoelectron fluxes with measured photoelectron spectra is used to gain further insights into the estimation method and reveals consistent values within 10–60 eV. Plain Language Summary: The impact of solar radiation on the atmosphere produces highly energetic electrons, which travel freely along the magnetic Earth's field lines from one hemisphere to the other. When these electrons flow from the sunlit side into the nightside hemisphere, they interact with the neutral species and produce noticeable effects in the ionosphere such as an increase in electron temperature and enhancement of airglow emissions. This study presents a method to quantify the amount of precipitating electrons and their energy on a global scale using two recent satellite missions, ICON and COSMIC2. Our results demonstrate that coincident far‐ultraviolet (ICON) and radio‐occultation (COSMIC2) measurements from space are valuable resources to study precipitating electrons in the ionosphere and their impact on inferring ionospheric plasma parameters. Key Points: Nightglow emissions excited by photoelectrons originating in the magnetically conjugate hemisphere are observed by the ICON mission Conjugate photoelectron energy spectra are derived for the first time using global scale far‐ultraviolet and radio‐occultation observations Comparison of estimated photoelectron fluxes with measurements on a rocket flight shows consistent characteristics at all altitudes